System and method for preventing iron injection into a proton exchange membrane in a fuel cell

CN117594845BActive Publication Date: 2026-10-27GM GLOBAL TECHNOLOGY OPERATIONS LLC
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202310119094.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Priority Date
2022-08-15
Filing Date
2023-01-31
Publication Date
2026-10-27
Estimated Expiration
2043-01-31

Smart Images

  • Figure CN117594845B_ABST
    Figure CN117594845B_ABST
Patent Text Reader

Abstract

A system for minimizing iron injection in a fuel cell includes a catalyst coated on a catalyst coated membrane (CCM) having a plurality of side edge portions. The CCM includes a membrane having a first planar side and a second planar side, an anode on the first planar side of the membrane, and a cathode on the second planar side of the membrane. The system also includes an anode gas diffusion layer (GDL) including a first microporous layer. The first microporous layer is in contact with the anode. The system also includes a cathode GDL including a second microporous layer. The second microporous layer is in contact with the cathode. The system also includes an adhesive in contact with the plurality of side edge portions of the CCM. The first microporous layer, the second microporous layer, and the adhesive collectively encapsulate the CCM and minimize iron injection into the membrane.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This disclosure generally relates to systems and methods for preventing or minimizing iron injection into proton exchange membranes in fuel cells. Background Technology

[0002] A fuel cell uses a stream of hydrogen or another fuel and a stream of oxygen to generate electricity. A fuel cell includes at least one pair of anode and cathode electrodes separated by a proton exchange membrane (PEM). An electrochemical reaction occurs when hydrogen or another fuel is exposed to the anode, and when oxygen in the form of compressed air is exposed to the cathode. The PEM facilitates ion exchange between the anode and cathode that can be used for the electrochemical reaction. Summary of the Invention

[0003] A system for minimizing iron injection in a fuel cell is provided. The system includes a catalyst coated on a proton exchange membrane (CCM) having multiple side edge portions. The CCM includes a proton exchange membrane having a first planar side and a second planar side, an anode electrode on the first planar side of the proton exchange membrane, and a cathode electrode on the second planar side of the proton exchange membrane. The system also includes an anolyte gas diffusion layer (GDL) comprising a first microporous layer, wherein the first microporous layer is configured to contact the anode electrode. The system also includes a cathode GDL comprising a second microporous layer, wherein the second microporous layer is configured to contact the cathode electrode. The system further includes an adhesive in contact with the multiple side edge portions of the CCM. The first microporous layer, the second microporous layer, and the adhesive collectively encapsulate the CCM and minimize iron injection into the proton exchange membrane.

[0004] In some embodiments, the first microporous layer and the second microporous layer are each composed of conductive carbon particles bonded together with a polymer having hydrophobic properties.

[0005] In some embodiments, the polymer is polytetrafluoroethylene (PTFE) or fluorinated ethylene propylene (FEP).

[0006] In some embodiments, the first microporous layer and the second microporous layer each have a pore size ranging from 50 nanometers to 150 nanometers.

[0007] In some embodiments, the adhesive has thermal creep properties.

[0008] In some embodiments, the system further includes a first sub-washer and a second sub-washer. A portion of the adhesive is disposed between the first sub-washer and the second sub-washer.

[0009] In some embodiments, the first microporous layer is configured to contact a portion of one of the anode or cathode electrodes. The adhesive is configured to contact the remainder of one of the anode or cathode electrodes.

[0010] According to an alternative embodiment, a system for minimizing iron injection is provided. The system includes an apparatus comprising a fuel cell configured to supply electrical energy to the apparatus. The fuel cell includes a catalyst coated on a proton exchange membrane (CCM) having multiple side edges. The CCM includes a proton exchange membrane having a first planar side and a second planar side, an anode electrode on the first planar side of the proton exchange membrane, and a cathode electrode on the second planar side of the proton exchange membrane. The fuel cell also includes an anode gas diffusion layer (GDL) comprising a first microporous layer, wherein the first microporous layer is configured to contact the anode electrode. The fuel cell also includes a cathode GDL containing a second microporous layer, wherein the second microporous layer is configured to contact the cathode electrode. The fuel cell also includes an adhesive in contact with the multiple side edge portions of the CCM. The first microporous layer, the second microporous layer, and the adhesive collectively encapsulate the CCM and minimize iron injection into the proton exchange membrane.

[0011] In some embodiments, the first microporous layer and the second microporous layer are each composed of conductive carbon particles bonded together with a polymer having hydrophobic properties.

[0012] In some embodiments, the first microporous layer and the second microporous layer each have a pore size ranging from 50 nanometers to 150 nanometers.

[0013] In some embodiments, the adhesive has thermal creep properties.

[0014] In some embodiments, the fuel cell further includes a first sub-wafer and a second sub-wafer. A portion of the adhesive is disposed between the first sub-wafer and the second sub-wafer.

[0015] In some embodiments, the first microporous layer is configured to contact a portion of one of the anode or cathode electrodes. The adhesive contacts the remainder of said anode or cathode electrode.

[0016] According to an alternative embodiment, a method is provided to prevent iron injection into a proton exchange membrane (CCM) in a fuel cell. The method includes depositing a first coating on an anode gas diffusion layer (GDL), wherein the first coating includes a first microporous layer. The method further includes depositing a second coating on a cathode GDL, wherein the second coating includes a second microporous layer. The method further includes disposing an adhesive and a catalyst coated on a proton exchange membrane (CCM) between the anode GDL and the cathode GDL. The CCM has multiple side edge portions and includes a proton exchange membrane having a first planar side and a second planar side. The CCM also includes an anode electrode on the first planar side of the proton exchange membrane and a cathode electrode on the second planar side of the proton exchange membrane. The method further includes applying heat and pressure to the anode GDL and the cathode GDL during a lamination process, such that the first microporous layer is positioned in contact with the anode electrode and the second microporous layer is positioned in contact with the cathode electrode. The lamination process extrudes and presses the adhesive into contact with the multiple side edge portions of the CCM. The method further includes encapsulating the CCM with the first microporous layer, the second microporous layer, and the adhesive to minimize iron injection into the proton exchange membrane.

[0017] In some embodiments, the method further includes forming a first microporous layer and a second microporous layer using conductive carbon particles bonded to a polymer having hydrophobic properties.

[0018] In some embodiments, the polymer is polytetrafluoroethylene (PTFE) or fluorinated ethylene propylene (FEP).

[0019] In some embodiments, the first microporous layer and the second microporous layer each include pore sizes ranging from 50 nanometers to 150 nanometers.

[0020] In some embodiments, applying heat and pressure reduces the viscosity of the adhesive.

[0021] In some embodiments, the method further includes positioning a first sub-wafer and a second sub-wafer along a plurality of side edge portions of the CCM. A portion of the adhesive is disposed between the first sub-wafer and the second sub-wafer.

[0022] In some embodiments, the first microporous layer is configured to contact a portion of either the anode or cathode electrode. The lamination process further presses the adhesive into contact with the remaining portions of the anode and cathode electrodes.

[0023] This invention provides the following technical solutions:

[0024] 1. A system for minimizing iron injection in a fuel cell, the system comprising:

[0025] A catalyst coated on a proton exchange membrane (CCM), the proton exchange membrane having multiple side edge portions and comprising:

[0026] A proton exchange membrane having a first planar side and a second planar side;

[0027] The anode electrode on the first planar side of the proton exchange membrane; and

[0028] The cathode electrode on the second planar side of the proton exchange membrane; and

[0029] An anolyte gas diffusion layer (GDL) including a first microporous layer, wherein the first microporous layer is configured to contact the anode electrode;

[0030] The cathode GDL includes a second microporous layer, wherein the second microporous layer is configured to contact the cathode electrode; and

[0031] Adhesive in contact with multiple side edge portions of the CCM; and

[0032] The first microporous layer, the second microporous layer, and the adhesive together encapsulate the CCM and minimize the iron injected into the proton exchange membrane.

[0033] 2. The system according to technical solution 1, wherein the first microporous layer and the second microporous layer are each composed of conductive carbon particles bonded together with a hydrophobic polymer.

[0034] 3. The system according to technical solution 2, wherein the polymer is polytetrafluoroethylene (PTFE) or fluorinated ethylene propylene (FEP).

[0035] 4. The system according to technical solution 2, wherein the first microporous layer and the second microporous layer each have a pore size from 50 nanometers to 150 nanometers.

[0036] 5. The system according to technical solution 1, wherein the adhesive has thermal creep properties.

[0037] 6. The system according to technical solution 1 further includes:

[0038] First washer; and

[0039] Second washer; and

[0040] A portion of the adhesive is disposed between the first sub-wafer and the second sub-wafer.

[0041] 7. The system according to technical solution 1, wherein the first microporous layer is configured to contact a portion of either the anode electrode or the cathode electrode; and

[0042] The adhesive is configured to contact the remainder of either the anode electrode or the cathode electrode.

[0043] 8. A system for minimizing iron injection, the system comprising:

[0044] The apparatus includes:

[0045] A fuel cell, configured to provide electrical energy to the device, and comprising:

[0046] A catalyst coated on a proton exchange membrane (CCM), the proton exchange membrane having multiple side edges and comprising:

[0047] A proton exchange membrane having a first planar side and a second planar side;

[0048] The anode electrode on the first planar side of the proton exchange membrane; and

[0049] The cathode electrode on the second planar side of the proton exchange membrane; and the anolyte gas diffusion layer (GDL) including a first microporous layer, wherein the first microporous layer is configured to contact the anolyte electrode;

[0050] The cathode GDL includes a second microporous layer, wherein the second microporous layer is configured to contact the cathode electrode; and

[0051] Adhesive in contact with multiple side edge portions of the CCM; and

[0052] The first microporous layer, the second microporous layer, and the adhesive together encapsulate the CCM and minimize the iron injected into the proton exchange membrane.

[0053] 9. The system according to technical solution 8, wherein the first microporous layer and the second microporous layer are each composed of conductive carbon particles bonded together with a polymer having hydrophobic properties.

[0054] 10. The system according to technical solution 9, wherein the first microporous layer and the second microporous layer each have a pore size from 50 nanometers to 150 nanometers.

[0055] 11. The system according to technical solution 8, wherein the adhesive has thermal creep properties.

[0056] 12. The system according to technical solution 8, wherein the fuel cell further comprises:

[0057] First washer; and

[0058] Second washer; and

[0059] A portion of the adhesive is disposed between the first sub-wafer and the second sub-wafer.

[0060] 13. The system according to technical solution 8, wherein the first microporous layer is configured to contact a portion of one of the anode electrode or the cathode electrode; and

[0061] The adhesive is in contact with the remainder of either the anode electrode or the cathode electrode.

[0062] 14. A method for preventing iron injection into a proton exchange membrane in a fuel cell, the method comprising:

[0063] A first coating is deposited on an anodic gas diffusion layer (GDL), wherein the first coating includes a first microporous layer;

[0064] A second coating is deposited on the cathode GDL, wherein the second coating includes a second microporous layer;

[0065] An adhesive and a catalyst coated on a proton exchange membrane (CCM) are disposed between the anode GDL and the cathode GDL.

[0066] The CCM has multiple side edge portions and includes:

[0067] The proton exchange membrane has a first planar side and a second planar side.

[0068] The anode electrode on the first planar side of the proton exchange membrane, and

[0069] The cathode electrode on the second planar side of the proton exchange membrane; and

[0070] During the lamination process, heat and pressure are applied to the anode GDL and the cathode GDL, such that the first microporous layer is positioned in contact with the anode electrode and the second microporous layer is positioned in contact with the cathode electrode, wherein the lamination process extrudes the adhesive and presses the adhesive into contact with a plurality of side edge portions of the CCM; and

[0071] The CCM is encapsulated by the first microporous layer, the second microporous layer, and the adhesive, thereby minimizing the iron injected into the proton exchange membrane.

[0072] 15. The method according to technical solution 14 further includes forming the first microporous layer and the second microporous layer with conductive carbon particles bonded to a polymer having hydrophobic properties.

[0073] 16. The method according to technical solution 15, wherein the polymer is polytetrafluoroethylene (PTFE) or fluorinated ethylene propylene (FEP).

[0074] 17. The method according to technical solution 15, wherein the first microporous layer and the second microporous layer each include a pore size in the range of 50 nanometers to 150 nanometers.

[0075] 18. The method according to technical solution 14, wherein applying heat and pressure reduces the viscosity of the adhesive.

[0076] 19. The method according to technical solution 14 further includes:

[0077] Position the first and second sub-washers along multiple side edge portions of the CCM;

[0078] A portion of the adhesive is disposed between the first sub-wafer and the second sub-wafer.

[0079] 20. The method according to technical solution 14, wherein the first microporous layer is configured to contact a portion of one of the anode electrode or the cathode electrode; and

[0080] The lamination process further presses the adhesive into contact with the remainder of either the anode or cathode electrode.

[0081] The foregoing features and advantages, as well as other features and advantages, of this disclosure will become apparent when taken in conjunction with the accompanying drawings from the following detailed description of the best mode for carrying out this disclosure. Attached Figure Description

[0082] Figure 1 A system for preventing iron injection into a proton exchange membrane in a fuel cell, according to the present disclosure, is illustrated schematically.

[0083] Figure 2 The following diagram schematically illustrates the lamination process prior to the present disclosure. Figure 1 The system;

[0084] Figure 3 The illustration schematically shows a scaled-up version of the present disclosure. Figure 1 The system;

[0085] Figure 4 The illustration schematically depicts an apparatus for a vehicle comprising a fuel cell stack, according to an embodiment of the present disclosure. Figure 1 The system; and

[0086] Figure 5 This is a flowchart illustrating a method for preventing iron injection into a proton exchange membrane in a fuel cell according to the present disclosure. Detailed Implementation

[0087] Proton exchange membranes (PEMs) facilitate ion transfer between the anode and cathode in fuel cells. A PEM can be positioned between the anode and cathode to prevent direct contact while allowing ion transfer, or, in the case of a hydrogen reaction at the anode, to facilitate ion transfer. + Or protons are transferred across the proton exchange membrane.

[0088] Fuel cell stack components can be made of a variety of materials. Steel can be used in parts of the fuel cell stack, such as bipolar plates. Due to corrosion of steel components, iron (Fe[II]) in cationic form can be present within the fuel cell stack. Hydroxyl radicals (OH·) that attack the PEM can also be induced by a reaction described as the Fenton reaction, in which hydrogen peroxide decomposes into OH· in the presence of (Fe[II]). As a result of this radical attack, the efficiency of the PEM and other factors can be reduced.

[0089] Iron released through plate corrosion enters the proton exchange membrane via two pathways. One pathway is through the gas diffusion layer (GDL). The other is via the edge of the integrated electrode assembly (UEA), where the proton exchange membrane can be exposed to the bypass region.

[0090] The disclosed system and method prevent iron injection into the proton exchange membrane in two ways. First, the system and method include the use of a sub-gasket adhesive material, thickness, and lamination process that allows the adhesive to deform or extend into the region between the GDL and the sub-gasket to seal the edges of the UEA and the proton exchange membrane during and as a result of the lamination process. Second, the disclosed system and method include providing a microporous layer (MPL) between the GDL and a catalyst coated on the proton exchange membrane (CCM) to block iron transport pathways into the proton exchange membrane.

[0091] The disclosed system includes a catalyst coated on a proton exchange membrane (CCM) having multiple side edge portions. The CCM includes a proton exchange membrane having a first planar side and a second planar side, an anode electrode on the first planar side of the proton exchange membrane, and a cathode electrode on the second planar side of the proton exchange membrane. The system also includes an anolyte gas diffusion layer (GDL) comprising a first microporous layer, wherein the first microporous layer is configured to contact the anode electrode. The system also includes a cathode GDL comprising a second microporous layer, wherein the second microporous layer is configured to contact the cathode electrode. The system further includes an adhesive in contact with the multiple side edge portions of the CCM. The first microporous layer, the second microporous layer, and the adhesive collectively encapsulate the CCM and minimize iron injection into the proton exchange membrane.

[0092] In one embodiment, the system includes a diffusion medium (DM), an MPL, and a CCM having at least one sub-waist and an adhesive material. The adhesive material has thermal creep properties and can be used to cover edge areas. When the adhesive is heated above average room temperature, the thermal creep adhesive material exhibits reduced viscosity. In one embodiment, the adhesive can be stable or relatively viscous at room temperature, and when heated to the temperature used in the lamination process, the adhesive can reduce its viscosity to a level that allows it to flow into grooves in the disclosed system in response to compressive forces applied to the system during the lamination process. Iron injection is not permitted in the adhesive material. The MPL comprises conductive carbon particles bonded to a polymer with hydrophobic properties, such as polytetrafluoroethylene (PTFE) or fluorinated ethylene propylene (FEP). In one embodiment, the pore size of the MPL is from 50 nm to 150 nm, for example from 75 nm to 125 nm, or from 90 nm to 110 nm, or 100 nm.

[0093] The disclosed systems and methods can improve proton exchange membrane life and fuel cell durability for heavy-duty truck or commercial truck applications.

[0094] The first and second microporous layers can each be composed of conductive carbon particles bonded together by a hydrophobic polymer. The polymer can be polytetrafluoroethylene (PTFE) or fluorinated ethylene propylene (FEP).

[0095] The first and second microporous layers can each have a pore size ranging from 50 nanometers to 150 nanometers.

[0096] Adhesives can have thermal creep properties.

[0097] The disclosed system may also include a first sub-washer and a second sub-washer. A portion of the adhesive may be disposed between the first sub-washer and the second sub-washer.

[0098] The first microporous layer may be configured to contact a portion of either the anode or cathode electrode. The adhesive may be configured to contact the remainder of either the anode or cathode electrode.

[0099] Referring now to the accompanying drawings, in which the same reference numerals denote the same features in several views. Figure 1A system 10 for preventing iron injection into a proton exchange membrane 40 in a fuel cell is schematically shown. System 10 includes an anode gas diffusion layer (GDL) 20, a cathode GDL 30, and a proton exchange membrane 40. Both the anode GDL 20 and the cathode GDL 30 are configured for the diffusion of hydrogen and air into the CCM 45, respectively, and for the delivery of liquid water from the CCM 45 to the flow channels. The proton exchange membrane 40 is a planar material having a flat or planar top and bottom surface and multiple side edge portions 46. An anode 42 and a cathode 44 are coated on the flat top and bottom surfaces of the proton exchange membrane 40, respectively. The anode 42 can be described as an anode electrode, and the cathode 44 can be described as a cathode electrode. The anode 42, cathode 44, and proton exchange membrane 40 can be collectively referred to as the CCM 45.

[0100] An electrolyte is provided within system 10, which serves as an exchange medium through which protons travel from the anode 42 to the cathode 44. Over time, iron from corrosion of fuel reactor components can enter the electrolyte solution and pose a risk of degradation to the proton exchange membrane 40.

[0101] A first microporous layer 22 is disposed on the anode GDL 20. A second microporous layer 32 is disposed on the cathode GDL 30. Microporous layers 22 and 32 comprise conductive carbon particles bonded to a polymer having hydrophobic properties. In one embodiment, the pore size of microporous layers 22 and 32 is from 50 nm to 150 nm, for example from 75 nm to 125 nm, or from 90 nm to 110 nm, or 100 nm. Microporous layers 22 and 32 are each configured to discharge water vapor generated from the anode 42 and cathode 44, which passes through the anode GDL 20 and cathode GDL 30, respectively. The pore size and hydrophobic properties of microporous layers 22 and 32 prevent iron dissolved in liquid water from passing through microporous layers 22 and 32. In the region where microporous layer 22 contacts the anode 42 of CCM 45, microporous layer 22 prevents iron released from corrosion of bipolar plates or other iron-containing components in the fuel cell stack from contacting CCM 45. In the region where the microporous layer 32 contacts the cathode 44, the microporous layer 32 prevents iron released from corrosion of bipolar plates or other iron-containing components in the fuel cell stack from contacting the CCM 45.

[0102] System 10 may also include sub-gaskets 50 and 52. Sub-gaskets 50 and 52 are shown positioned very close to the anode GDL 20, cathode GDL 30, and CCM 45. The sub-gaskets are designed to anchor and seal the CCM 45 between two bipolar plates (BPP) that receive or enclose the system 10 from above and below. Adhesive 54 is disposed between sub-gaskets 50 and 52. Sub-gaskets 50 and adhesive 54 are shown disposed between the microporous layer 22 of the anode GDL 20 and the CCM 45. Adhesive 54 is provided, at least initially, in the form of a viscous liquid or paste during installation. During the lamination process, which uses heat and pressure to press the anode GDL 20 against the CCM 45, the adhesive is compressed between the sub-gasket 50, the microporous layer 22 of the anode GDL 20, and the CCM 45, causing the adhesive 54 to deform and be pressed into close contact with the CCM 45 and the microporous layer 22 of the anode GDL 20. The adhesive 54 contacts and abuts against the portion 47 of the anode 42 that is not in contact with the microporous layer 22, forming a seal. The adhesive 54 further deforms into an adhesive portion 56 that contacts and abuts against the edge portion 46 of the proton exchange membrane 40, forming a seal. The adhesive 54 is impermeable to iron, or prevents iron released from corrosion of bipolar plates or other iron-containing components in the fuel cell stack from contacting the proton exchange membrane 40. By sealing the portions of the CCM 45 that are not in contact with the microporous layers 22 and 32, the adhesive 54 prevents iron from contacting the proton exchange membrane 40.

[0103] The combination of microporous layers 22 and 32 and adhesive 54 encapsulates the CCM 45. Both microporous layers 22 and 32 and adhesive 54 prevent iron released by corrosion of the bipolar plates or other iron-containing components in the fuel cell stack of system 10 from passing through them, and thus prevent iron from contacting and degrading the proton exchange membrane 40 of the CCM 45.

[0104] In one embodiment, the microporous layer 22 may cover or contact the entire exposed flat surface of the anode 42 of the CCM 45. Figure 1 In one embodiment, the portion of the microporous layer 22 that contacts the CCM 45 is narrower than the total width of the CCM 45, such that a portion of the plane is covered by the microporous layer 22, and a portion of the plane is not covered by the microporous layer 22. Adhesive 54 is used to cover the portion of the plane not covered by the microporous layer 22. In an alternative embodiment, the positions of the anode 42 and cathode 44, and the corresponding GDL layers 20 and 30, can be reversed, such that the microporous layer 32 may only contact / cover a portion of the planar surface of the cathode 44, and the adhesive 54 may cover the remaining portion of the planar surface not covered by the microporous layer 32.

[0105] Sub-washers 50 and 52 are exemplary. One sub-washer 50 or 52 may be used, or more than two sub-washers 50 and 52 may be used. In one embodiment, sub-washers 50 and 52 are not present.

[0106] Figure 2 The diagram schematically illustrates the process prior to lamination. Figure 1 System 10. The anode GDL 20 is illustrated as a different combination from the cathode GDL 30 and CCM 45. Sub-wafer 50 and adhesive 54 coated thereon, along with the initially separated sub-wafer 52, are shown positioned between the anode GDL 20 and the cathode GDL 30 and CCM 45. Figure 1 As shown, during the lamination process, heat and pressure are used to press the anode GDL 20 against the combination of the cathode GDL 30 and CCM 45. As a result of this process, the adhesive 54 contacts and adheres to the sub-gasket 52, and the adhesive 54 is compressed and deformed into the space left between the anode GDL 20 (including the microporous layer 22), the cathode GDL 30 (including the microporous layer 32), and the CCM 45. The adhesive 54 covers the edge portion 46 of the proton exchange membrane 40. As a result of the lamination process, the CCM 45 is encapsulated between the microporous layers 22 and 32 of the anode GDL 20 and the cathode GDL 30 by the adhesive 54, preventing iron released by corrosion of the bipolar plates or other iron-containing components in the fuel cell stack of system 10 from contacting the proton exchange membrane 40.

[0107] Figure 3 Schematally shown at an enlarged scale Figure 1 System 10. Figure 1 The system 10 shown includes an anode GDL 20, a cathode GDL 30, and a proton exchange membrane 40. Anode 42 and cathode 44 are shown coated on a flat top surface and a flat bottom surface of the proton exchange membrane 40, respectively. Multiple side edge portions 46, 48, and 49 of the proton exchange membrane 40, anode 42, and cathode 44 are shown, respectively. Gaskets 50 and 52 are shown, including an adhesive 54 disposed between them. The adhesive 54 is further shown deformed and sealing against the side edge portions 46 of the proton exchange membrane 40, the side edge portions 48 and 49 of the anode 42 and cathode 44, and the microporous layer of the anode GDL 20.

[0108] Figure 4 An apparatus 100 is schematically shown as being implemented as a vehicle including a fuel cell stack 110, the fuel cell stack 110 including... Figure 1System 10. Device 100 is shown as including a fuel cell stack 110, a hydrogen fuel storage tank 120, an intake manifold 130, a battery 140, and a motor 150 configured to provide output torque to an output component 152 using electrical energy. The fuel cell stack 110 may include multiple fuel cells repeatedly stacked within the fuel cell stack 110. Figure 1 System 10. The fuel cell stack 110 may include one or more steel components that provide structure and rigidity for the fuel cell stack 110. The fuel cell stack 110 receives a flow of hydrogen or other fuel gas from a hydrogen fuel storage tank 120 and a flow of air including oxygen from an intake manifold 130. The fuel cell stack 110 may include an air compressor device for pressurizing the air to a desired pressure. The fuel cell stack 110 may directly supply electrical energy to an electric motor 150, and / or the fuel cell stack 110 may supply electrical energy to a battery 140 for storage and later use. An output component 152 may provide output torque for, for example, providing prime mover power to the device 100. The device 100 may be implemented in other embodiments, such as a power generation unit, a boat, or other similar device.

[0109] According to an alternative embodiment of the disclosed system, the system includes an apparatus comprising a fuel cell configured to provide electrical energy to the apparatus. The fuel cell includes a catalyst coated on a proton exchange membrane (CCM) having multiple side edges. The CCM includes a proton exchange membrane having a first planar side and a second planar side, an anode electrode on the first planar side of the proton exchange membrane, and a cathode electrode on the second planar side of the proton exchange membrane. The fuel cell also includes an anode gas diffusion layer (GDL) comprising a first microporous layer, wherein the first microporous layer is configured to contact the anode electrode. The fuel cell also includes a cathode GDL comprising a second microporous layer, wherein the second microporous layer is configured to contact the cathode electrode. The fuel cell also includes an adhesive in contact with the multiple side edge portions of the CCM. The first microporous layer, the second microporous layer, and the adhesive collectively encapsulate the CCM and minimize iron injection into the proton exchange membrane.

[0110] The first and second microporous layers can each be composed of conductive carbon particles bonded together with a hydrophobic polymer.

[0111] The first and second microporous layers can each have a pore size ranging from 50 nanometers to 150 nanometers.

[0112] Adhesives can have thermal creep properties.

[0113] The fuel cell may also include a first sub-wafer and a second sub-wafer. A portion of the adhesive may be disposed between the first sub-wafer and the second sub-wafer.

[0114] The first microporous layer can be configured to contact a portion of either the anode or cathode electrode. The adhesive can contact the remainder of either the anode or cathode electrode.

[0115] Figure 5 This is a flowchart illustrating method 200 for preventing iron injection into the proton exchange membrane 40 of the fuel cell stack 110. Method 200 is relative to... Figure 1 System 10 components and Figure 4 The method is described using a fuel cell stack, although the physical components used in method 200 may include alternative embodiments. Method 200 begins at step 202. In step 204, for Figure 1 The anode GDL20 provides a microporous layer 22, for Figure 1 The cathode GDL 30 provides a microporous layer 32, and a proton exchange membrane 40 is placed between the anode 42 and the cathode 44. In step 206, the anode GDL 20, cathode GDL 30, CCM 45, sub-wafers 50 including adhesive 54, and the initially separated sub-wafers 52 are aligned in preparation for the lamination process. In step 208, heat and pressure are applied to the aligned components, and the components are laminated together. As a result of this lamination process, adhesive 54 is squeezed and pressed into the grooves or cavities between the components. As a result of the lamination process, a portion of the CCM 45 is covered with the microporous material, and the remainder or remaining portion of the CCM 45 is coated or covered with adhesive 54. In step 210, the creation... Figure 3 The fuel cell stack 110 includes multiple iterations of system 10 (each iteration including a pair of anodes 42 and cathodes 44) into the fuel cell stack 110 to facilitate ion or proton transfer between the anode and cathode pairs within the fuel cell stack 110. Method 200 ends at step 212. Method 200 is provided as an exemplary method for preventing iron injection into the proton exchange membrane 40 within the fuel cell stack 110. Additional or alternative method steps may be employed, and this disclosure is not intended to be limited to the examples provided herein.

[0116] The disclosed method includes depositing a first coating on an anolyte gas diffusion layer (GDL), wherein the first coating includes a first microporous layer. The method further includes depositing a second coating on a cathode GDL, wherein the second coating includes a second microporous layer. The method further includes placing an adhesive and a catalyst coated on a proton exchange membrane (CCM) between the anolyte GDL and the cathode GDL. The CCM has multiple side edge portions and includes a proton exchange membrane having a first planar side and a second planar side. The CCM also includes an anode electrode on the first planar side of the proton exchange membrane and a cathode electrode on the second planar side of the proton exchange membrane. The method further includes applying heat and pressure to the anolyte GDL and the cathode GDL during a lamination process, such that the first microporous layer is positioned in contact with the anode electrode and the second microporous layer is positioned in contact with the cathode electrode. The lamination process extrudes and presses the adhesive into contact with the multiple side edge portions of the CCM. The method further includes encapsulating the CCM with the first microporous layer, the second microporous layer, and the adhesive to minimize iron injection into the proton exchange membrane.

[0117] The method may also include forming a first microporous layer and a second microporous layer using conductive carbon particles bonded to a hydrophobic polymer.

[0118] The polymer may include polytetrafluoroethylene (PTFE) or fluorinated ethylene propylene (FEP).

[0119] The first and second microporous layers may each include pore sizes ranging from 50 nanometers to 150 nanometers.

[0120] Applying heat and pressure can reduce the viscosity of adhesives.

[0121] The method may further include positioning a first sub-washer and a second sub-washer along multiple side edge portions of the CCM. A portion of the adhesive may be disposed between the first sub-washer and the second sub-washer.

[0122] The first microporous layer can be configured to contact a portion of either the anode or cathode electrode. The lamination process can further press the adhesive into contact with the remaining portion of either the anode or cathode electrode.

[0123] While the best mode of implementing this disclosure has been described in detail, those skilled in the art will recognize various alternative designs and embodiments for implementing this disclosure within the scope of the appended claims.

Claims

1. A system for minimizing iron injection in a fuel cell, the system comprising: A proton exchange membrane coated with a catalyst, the proton exchange membrane having multiple side edge portions and comprising: A proton exchange membrane having a first planar side and a second planar side; The anode electrode on the first planar side of the proton exchange membrane; and The cathode electrode on the second planar side of the proton exchange membrane; and An anode gas diffusion layer including a first microporous layer, wherein the first microporous layer is configured to contact the anode electrode; A cathode gas diffusion layer including a second microporous layer, wherein the second microporous layer is configured to contact the cathode electrode; A first sub-wafer is configured to contact the first microporous layer; and An adhesive that contacts multiple side edge portions of the proton exchange membrane coated with the catalyst; The anode electrode has a planar surface configured to contact the first microporous layer and the adhesive. Wherein, a first portion of the planar surface is configured to contact the first microporous layer, while the remaining portion of the planar surface is configured to contact the adhesive instead of the first microporous layer; and The first microporous layer, the second microporous layer, and the adhesive together encapsulate the proton exchange membrane coated with the catalyst and minimize the iron injected into the proton exchange membrane. The first microporous layer and the second microporous layer are each composed of conductive carbon particles bonded together with a hydrophobic polymer.

2. The system according to claim 1, wherein, The polymer is polytetrafluoroethylene or fluorinated ethylene propylene.

3. The system according to claim 1, wherein, The first microporous layer and the second microporous layer each have a pore size ranging from 50 nanometers to 150 nanometers.

4. The system according to claim 1, wherein, The adhesive has thermal creep properties.

5. The system according to claim 1, further comprising: Second washer; and A portion of the adhesive is disposed between the first sub-wafer and the second sub-wafer.

6. A system for minimizing iron injection, the system comprising: The apparatus includes: A fuel cell, configured to provide electrical energy to the device, and comprising: A proton exchange membrane coated with a catalyst, the proton exchange membrane having multiple side edges and comprising: A proton exchange membrane having a first planar side and a second planar side; The anode electrode on the first planar side of the proton exchange membrane; and The cathode electrode on the second planar side of the proton exchange membrane; and An anode gas diffusion layer including a first microporous layer, wherein the first microporous layer is configured to contact the anode electrode; A cathode gas diffusion layer including a second microporous layer, wherein the second microporous layer is configured to contact the cathode electrode; A first sub-wafer is configured to contact the first microporous layer; and An adhesive that contacts multiple side edge portions of the proton exchange membrane coated with the catalyst; The anode electrode has a planar surface configured to contact the first microporous layer and the adhesive. Wherein, a first portion of the planar surface is configured to contact the first microporous layer, and the remaining portion of the planar surface is configured to contact the adhesive instead of the first microporous layer; and The first microporous layer, the second microporous layer, and the adhesive together encapsulate the proton exchange membrane coated with the catalyst and minimize the iron injected into the proton exchange membrane. The first microporous layer and the second microporous layer are each composed of conductive carbon particles bonded together with a hydrophobic polymer.

7. The system according to claim 6, wherein, The first microporous layer and the second microporous layer each have a pore size ranging from 50 nanometers to 150 nanometers.

8. The system according to claim 6, wherein, The adhesive has thermal creep properties.

9. The system according to claim 6, wherein, The fuel cell further includes: Second washer; and A portion of the adhesive is disposed between the first sub-wafer and the second sub-wafer.

10. A method for preventing iron injection into a proton exchange membrane in a fuel cell, the method comprising: A first coating is deposited on the anolyte gas diffusion layer, wherein the first coating includes a first microporous layer; The first sub-washer is configured to contact the first microporous layer; A second coating is deposited on the cathode gas diffusion layer, wherein the second coating includes a second microporous layer; An adhesive and a proton exchange membrane coated with a catalyst are disposed between the anode gas diffusion layer and the cathode gas diffusion layer. The proton exchange membrane coated with the catalyst has multiple side edge portions and includes: The proton exchange membrane has a first planar side and a second planar side. The anode electrode on the first planar side of the proton exchange membrane, and The cathode electrode on the second planar side of the proton exchange membrane; and During lamination, heat and pressure are applied to the anode gas diffusion layer and the cathode gas diffusion layer, such that the first microporous layer is positioned to contact a first portion of the planar surface of the anode electrode, the first microporous layer is not positioned to contact the remaining portion of the planar surface, the remaining portion of the planar surface is positioned to contact the adhesive, and the second microporous layer is positioned to contact the cathode electrode, wherein the lamination process extrudes and presses the adhesive to contact a plurality of side edge portions of the catalyst-coated proton exchange membrane; and The proton exchange membrane coated with the catalyst is encapsulated by the first microporous layer, the second microporous layer and the adhesive, thereby minimizing the iron injected into the proton exchange membrane; The first and second microporous layers are formed using conductive carbon particles bonded to a polymer with hydrophobic properties.

11. The method according to claim 10, wherein, The polymer is polytetrafluoroethylene or fluorinated ethylene propylene.

12. The method according to claim 10, wherein, The first microporous layer and the second microporous layer each include pore sizes ranging from 50 nanometers to 150 nanometers.

13. The method according to claim 10, wherein, Applying heat and pressure reduces the viscosity of the adhesive.

14. The method of claim 10, further comprising: The second sub-wafer is positioned along multiple side edge portions of the proton exchange membrane coated with the catalyst; and A portion of the adhesive is disposed between the first sub-wafer and the second sub-wafer.

Citation Information

Patent Citations

  • Microporous layer structures and gas diffusion layer assemblies in proton exchange membrane fuel cells

    US20140272659A1

  • Diffusion medium for use in fuel cell, fuel cell and method of making the diffusion medium

    US20160172692A1

  • Fuel cell and method for manufacturing the fuel cell

    US20200280085A1